Selektivitas fraksi Rf < 0,5 ekstrak etil asetat (EtOAc) biji putat air (Barringtonia racemosa)terhadap keong mas (Pomacea canaliculata) dan ikan lele lokal (Clarias batrachus) - Musri Musman; Sofia F; Viqqi Kurnianda (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Research to determine the selectivity of fraction Rf 0.5 of ethyl acetate extract (EtOAc) of putat air kernel (Barringtonia racemosa) on golden apple snail(Pomacea canaliculata) and local catfish (Clarias batrachus) was conducted in February 2012 at the Laboratory of Chemistry of Teacher Training and Education Faculty and Laboratory of Marine Chemistry of Coordinatorate of Marine and Fisheries of Syiah Kuala University. Thin-layer chromatography was used to separate components in the extract samples, and testing of biological activity based on the procedures recommended by FAO. Golden apple snail and local catfish mortality data were analyzed using Probit program, and value of selectivity (S) was processed according to the Wang and Fengs formula.The values of LC50 of the fraction Rf 0.5 were 29.26 ppm for P. canaliculata and 44.47 ppm for C. batracus. The selectivity value for the tested organisms was 1.51. This study revealed that the tested extract has bioactive property as molluscicide of P. canaliculata.Key words. Biological activity, thin-layer chromatography, mortality, bioactive property, molluscicide, LC50.